Membincangkan Anak-anak dalam Iklan Pertamina versi Pemanfaatan Energi - Arzak, Miftahul (Jurnal Komunikator, 2015)
This paper aims to explain the hidden meaning behind the ad of Pertamina, namely âPemanfaatan Energi (Energy Utilization)â.Â  The ad displays childrens as models and narratives filled by children in the form of audio and texts. This paper thus will analyze text, audio and display of children within the Pertaminas ad. It will be analyzed using the concept of Nature as Backdrop and Environmental Advocacy by Julia B Corbett, which argues that the ad is a message that is made to attract attention, and to give understanding to the audience. At the end, this paper explicates howÂ  children are displayed in the Pertaminas ad.Â Keyword: Pertamina, Children, Ad